Religious coping among psychotic patients: Relevance to suicidality and treatment outcomes - Rosmarin, David H.; Bigda-Peyton, Joseph S.; Öngur, Dost; Pargament, Kenneth I.; Björgvinsson, Thröstur (Psychiatry research, 2013)
Religious coping is very common among individuals with psychosis, however its relevance to symptoms and treatment outcomes remains unclear. We conducted a prospective study in a clinical sample of n=47 psychiatric patients with current/past psychosis receiving partial (day) treatment at McLean Hospital. Subjects completed measures of religious involvement, religious coping and suicidality prior to treatment, and we assessed for psychosis, depression, anxiety and psychological well-being over the course of treatment. Negative religious coping (spiritual struggle) was associated with substantially greater frequency and intensity of suicidal ideation, as well as greater depression, anxiety, and less well-being prior to treatment (accounting for 9.0–46.2% of the variance in these variables). Positive religious coping was associated with significantly greater reductions in depression and anxiety, and increases in well-being over the course of treatment (accounting for 13.7–36.0% of the variance in change scores). Effects remained significant after controlling for significant covariates. Negative religious coping appears to be a risk factor for suicidality and affective symptoms among psychotic patients. Positive religious coping is an important resource to this population, and its utilization appears to be associated with better treatment outcomes.